Effect of dietary restriction on health span in Caenorhabditis elegans: A systematic review - Jazween Loo; Muhammad Arif Fikri Shah Bana; Jen Kit Tan; Jo Aan Goon (Experimental Gerontology, 2023)
Dietary restriction (DR) interventions have demonstrated their efficacy in extending lifespan; however, the association between lifespan extension and health span remains unclear. This article aims to analyze the relationship between DR-induced lifespan and health span in Caenorhabditis elegans (C. elegans), a widely used animal model in lifespan studies. By examining various parameters such as lipofuscin accumulation (an aging marker) and locomotor and feeding capacities (indicators of muscle degradation rate), we have compiled papers that investigate and report on these DR-induced effects.The majority of the papers reviewed consistently demonstrate that DR improves both lifespan and health span in C. elegans. Worms subjected to DR exhibit slower lipofuscin accumulation compared to those fed ad libitum, indicating a reduction in age-related cellular damage. Additionally, DR-treated worms display a higher locomotion capacity, suggesting a slower rate of muscle degradation. However, it is worth noting that there are some discrepancies among the papers regarding feeding capacity. These contradictions can be attributed to the different methods employed to initiate DR. While many approaches slow muscle degeneration and enhance pumping rates through adaptation to limited food sources, other methods, such as using eat-2 mutant worms or interventions that mimic the effects of eat-2, reduce feeding capacity and consequently restrict food intake. In conclusion, the findings suggest a strong correlation between DR-induced longevity and the extension of health span in C. elegans, as evidenced by improvements in various health span parameters. DR interventions not only extend lifespan but also mitigate age-related markers and preserve locomotor capacity. Although conflicting results are observed regarding feeding capacity, the overall evidence supports the notion that DR promotes healthier aging in this animal model.